Property rights and intellectual property protection, GDP growth and individual well-being in Latin America - Amina Ahmed Lahsen; Alan T. Piper (Latin American Economic Review, 2019)
A central argument for increased protections of property rights (PR) is the role they play in encouraging economic transactions, investment and economic growth. Likewise, the utilitarian justification of intellectual property laws is that such rights promote creative inventions and innovation, and thus can make a nation better off. A further argument is psychological: it has also been argued (though rarely tested) that enhanced rights contribute to increases in well-being enjoyed by a country's citizens. Many Latin American countries have made efforts to improve property rights (and their enforcement) in the recent past, with varying success. Using three data sources (the Latinobarometer, the World Bank, and the World Economic Forum's Global Competitive Index), this investigation considers the relationship between property rights and intellectual property protection, economic growth, and individual well-being. The results, which are heterogeneous with respect to labour force status, suggest that policy makers in Latin America should pursue improvements in property rights if they wish to improve citizen well-being while also promoting economic growth.
Keywords: D23; I31; N36; O34; 330; Property rights; Intellectual property protection; Economic growth; Latin America; Life satisfaction; Latinobarometer